Premature and multiple births in IVF are associated with pretreatment circulating LH/hCG receptor concentration. (2nd October 2017) - Chambers, Anne; Fairbairn, Craig; Gaudoin, Marco; Mills, Walter; Banerjee, Subhasis
Abstract: The luteinizing hormone (LH) and pregnancy hormone, human chorionic gonadotrophin (hCG), share a common receptor: LH/hCG-R or LHCGR. In this prospective study involving 290 patients undergoing in vitro fertilization (IVF) and embryo transfer, we have examined whether pretreatment circulating LHCGR (sLHCGR) influences the course of pregnancy and perinatal outcome after embryo transfer. The blood samples were collected before the fertility treatment began and sLHCGR concentrations were measured using an enzyme-linked immunosorbent assay (ELISA) test. We demonstrate that extreme pretreatment sLHCGR concentrations (low & high) were linked to abnormal birth weights for singleton births, while very low concentrations of sLHCGR were associated with premature delivery (≤34 weeks) of singletons and multiple births following transfer of ≥2 embryos.